Comparison of Some Properties of Soils Under Different Land Uses: The Case Study of Zonguldak-Eregli, Turkiye - Bolat, İlyas; Ozkale, Muhammet Bartu; Şensoy, Hüseyin; Bolat, İlyas; Şensoy, Hüseyin (Aves, 2025)
Changes in land use and management practices often alter the morphological, physical, chemical, and biological properties of the soil. The present study was initiated and conducted in Ere & gbreve;li district of Zonguldak province to evaluate the effects of land use on some physical and chemical properties of soil. Two neighboring land use types were considered for the study: Sessile oak forest area and common hazelnut orchard. For the soil analysis, a total of 14 soil samples were taken from the fields, with a simple random sample taken in equal numbers, from a depth of 0-20 cm. The analysis results were evaluated using an independent T-test with a confidence interval of .05. The results indicated that there was a statistical difference (p < .05) between some physical properties of the soil in the land use patterns. Similarly, it was found that there was a statistical difference (p < .05) between the chemical properties of soils, electrical conductivity, calcium carbonate, and soil reaction, but it was determined that there was no statistical difference (p > .05) between organic C, total N, Corg/Ntotal ratio, available P, and K. On the other hand, the organic C (average 10.23 g kg-1), total N (average 1.06 g kg-1) and available P (average 3.45 kg da-1) contents of the soils in the oak forest area are higher than these properties of the soils in the hazelnut orchard. In contrast, the average available K content of the soils in the hazelnut orchard is higher (average 49.73 kg da-1) than in the oak forest area. Consequently, the determination of soil properties in terms of physical and chemical characteristics such as soil reaction and some plant nutrients (especially C, N, P, K), as well as the determination of deficiency, surplus, and sufficiency values, is of great importance for soil management.
Keywords: Corylus Avellana L.; Land Use And Management; Sessile Oak; Soil Quality; Western Black Sea